Berberis vulgaris root extract alleviates the adverse effects of heat stress via modulating hepatic nuclear transcription factors in quails - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Borawska, Maria H.; Jablonski, Jakub; Guler, Osman; Hayirli, Armagan (Cambridge Univ Press, 2013)
To evaluate the action mode of Berberis vulgaris root extract in the alleviation of oxidative stress, female Japanese quails (n 180, aged 5 weeks) were reared, either at 22 degrees C for 24 h/d (thermoneutral, TN) or 34 degrees C for 8 h/d (heat stress, HS), and fed one of three diets: diets containing 0, 100 or 200mg of B. vulgaris root extract per kg for 12 weeks. Exposure to HS depressed feed intake by 8.5% and egg production by 12.1 %, increased hepatic malondialdehyde (MDA) level by 98.0% and decreased hepatic superoxide dismutase, catalase and glutathione peroxidase activities by 23.5, 35.4 and 55.7 %, respectively (P<0.001 for all). There were also aggravations in expressions of hepatic NF-kappa B and heat-shock protein 70 (HSP70) by 42 and 43 %, respectively and suppressions in expressions of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and haeme-oxygenase 1 (HO-1) by 57 and 61 %, respectively, in heat-stressed quails (P<0.001 for all). As supplemental B. vulgaris extract increased, there were linear increases in performance parameters, activities of antioxidant enzymes and hepatic Nrf2 and HO-1 expressions (P<0.001 for all) and linear decreases in hepatic MDA level and NF-kappa B and HSP70 expressions at a greater extent in quails reared under TN condition and those reared under HS condition. In conclusion, dietary supplementation of B. vulgaris root extract to quails reduces the detrimental effects of oxidative stress and lipid peroxidation resulting from HS via activating the host defence system at the cellular level.
Keywords: Berberis vulgaris; Oxidative stress; Biomarkers; Defence system; Nuclear transcription factors; Heat stress